Psychosocial stress and ovarian function in adolescent and young adult cancer survivors. Issue 2 (5th December 2020) - Kim, Jayeon; Whitcomb, Brian W; Kwan, Brian; Zava, David; Sluss, Patrick M; Dietz, Andrew; Shliakhtsitsava, Ksenya; Romero, Sally A D; Natarajan, Loki; Su, H Irene
Abstract: STUDY QUESTION: Is psychosocial stress associated with ovarian function in reproductive-aged survivors of cancer diagnosed as adolescents and young adults (AYA survivors)? SUMMARY ANSWER: We observed no association between self-reported and biomarkers of psychosocial stress and ovarian function in AYA survivors. WHAT IS KNOWN ALREADY: Psychosocial stress suppresses hypothalamic-pituitary-ovarian axis, resulting in ovulatory dysfunction, decreased sex steroidogenesis and lower fertility in reproductive-aged women. Many cancer survivors experience high psychosocial stress and hypothalamic-pituitary-adrenal axis dysregulation. The menstrual pattern disturbances and infertility they experience have been attributed to ovarian follicle destruction, but the contribution of psychosocial stress to these phenotypes is unknown. STUDY DESIGN, SIZE, DURATION: A cross-sectional study was conducted estimating the association between perceived stress, measured by self-report and saliva cortisol, and ovarian function, measured by bleeding pattern, dried blood spot (DBS) FSH and LH, and saliva estradiol. We included 377 AYA survivor participants. PARTICIPANTS/MATERIALS, SETTING, METHODS: AYA survivor participants were ages 15–35 at cancer diagnosis and ages 18–40 at study enrollment, had completed primary cancer treatment, had a uterus and at least one ovary, did not have uncontrolled endocrinopathy and were not on hormone therapy. Recruited from cancer registries, physician referrals and cancer advocacy groups, participants provided self-reported information on psychosocial stress (Perceived Stress Scale-10 (PSS-10)) and on cancer and reproductive (fertility, contraception, menstrual pattern) characteristics. DBS samples were collected timed to the early follicular phase (cycle Days 3–7) for menstruating individuals and on a random day for amenorrheic individuals; saliva samples were collected three time points within 1 day. FSH and LH were measured by DBS ELISAs, cortisol was measured by ELISA and estradiol was measured by liquid chromatography tandem mass spectrometry. MAIN RESULTS AND THE ROLE OF CHANCE: The median age of participants was 34.0 years (range 19–41) at a median of 6.0 years since cancer diagnosis. The most common cancer was breast (32.1%). Median PSS-10 score was 15 (range 0–36), with 5.3% scoring ≥26, the cut point suggestive of severe stress. Cortisol levels followed a diurnal pattern and cortisol AUC was negatively correlated with PSS-10 scores ( P  =   0.03). Neither PSS-10 scores nor cortisol AUC were associated with FSH, LH, estradiol levels or menstrual pattern. Waking and evening cortisol and the cortisol awakening response also were not related to ovarian function measures. LIMITATIONS, REASONS FOR CAUTION: Our analysis is limited by its cross-sectional nature, heterogeneity of cancer diagnosis and treatments and low prevalence of severe stress. WIDER IMPLICATIONS OF THE FINDINGS: The lack of association between psychosocial stress and a variety of ovarian function measures in female AYA cancer survivors suggests that psychosocial stress does not have a significant impact on the reproductive axis of AYA survivors. This finding is important in counseling this population on their menstrual pattern and family building plans. STUDY FUNDING/COMPETING INTEREST(S): NIH HD080952, South Korea Health Industry Development Institute HI18C1837 (JK). Dr A.D. works for Bluebird Bio, Inc., Dr D.Z. works for ZRT Labs and Dr P.M.S. works for Ansh Labs, which did not sponsor, support or have oversight of this research. Other authors report no competing interests. TRIAL REGISTRATION NUMBER: N/A